Incorporating patient-reported outcomes into shared decision-making in the management of patients with osteoarthritis of the knee: a hybrid effectiveness-implementation study protocol. Issue 2 (21st February 2022) - Lin, Eugenia; Uhler, Lauren M; Finley, Erin P; Jayakumar, Prakash; Rathouz, Paul J; Bozic, Kevin J; Tsevat, Joel
Abstract : Introduction: Osteoarthritis (OA) is a major clinical and public health concern. The primary surgical treatment of knee OA is total knee replacement (TKR), a procedure that aims to alleviate pain and restore physical function. TKR is expensive, however, and based on professional guidelines, inappropriately performed in up to a third of patients. Patient-reported outcome measures (PROMs) help evaluate treatment options by quantifying health outcomes that matter to patients and can thus inform shared decision-making (SDM) between patients and health professionals. Methods and analysis: This is a US-based 2-year, two-site hybrid type 1 study to assess clinical effectiveness and implementation of a machine learning-based patient decision aid (PDA) integrating patient-reported outcomes and clinical variables to support SDM for patients with knee OA considering TKR. Substudy 1: At one study site, a randomised controlled trial is evaluating the clinical effectiveness of the PDA and SDM process on decision quality as measured after the baseline consultation and treatment choice measured 3 and 6 months after the baseline visit among 200 patients with knee OA. Substudy 2: At a second study site, a qualitative assessment using principles of behaviour design and intervention mapping is evaluating the feasibility and acceptability of the PROMs, PDA and SDM process by interviewing seven health professionals and 25 patients before and 25 patients after PDA implementation. Ethics and dissemination: Ethics approval has been obtained from The University of Texas at Austin Institutional Review Board (protocol number: 2018-11-0042). Informed consent will be obtained from all participants. Study results will be disseminated through conference presentations, publications and professional societies. Trial registration number: NCT04805554 .